Potential for imitation as a dynamic capability of organisation = Potencjał imitacji jako dynamiczna zdolność organizacji - Krzakiewicz, Kazimierz; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
Until recently, what was treated as unique resources in strategic management were financial, human and other resources, and their uniqueness was examined mostly in quantitative terms. However, globalisation of economic processes has meant that a degree to which resources are unique determine their quality, as a result of which they cannot be evaluated solely in quantitative terms.
Keywords: dynamiczne zdolności; imitacje; potencjał imitacji; innowacje; dynamic capabilities; imitation; imitation potential; innovation